Balanced cable routing for offshore wind farms with obstacles. Issue 4 (14th May 2022) - Cazzaro, Davide; Pisinger, David
Abstract: The cable routing problem is the task of designing the minimum‐cost electrical network between the turbines of offshore wind farms while satisfying several constraints. It contributes to decreasing wind energy costs, favoring the green transition. This paper focuses on balanced cable routing, studying both branched and radial network topology. First, we propose a visibility graph to route cables around obstacles and boundaries present in the wind farm area. Next, we develop a novel Large Neighborhood Search (LNS) heuristic using neighborhoods of increasing complexity: swap, exchanging two turbines between root‐branches; double swap, exchanging two pairs of turbines; cycle swap, moving turbines between root‐branches; and re‐partition, re‐partitioning and re‐routing two adjacent root‐branches. We also extend the LNS heuristic to the unbalanced branched configuration to compare to existing literature. On average, it finds solutions of the same quality using two orders of magnitude less run‐time, improving the solutions in five cases.